Great achievements and new landscapes in medical cancer therapy - Gandía, Daniel (2019)
Chemotherapy rapidly proved its worth in different clinical cancer settings, begining with hematologic malignancies. Many pediatric and young adult tumors achieved complete remission with chemotherapy, but its use as concomitant, adjuvant and/or neoadjuvant treatment also resulted in beneficial results. The new milenium developed new techniques in molecular drug design creating novel drugs specially directed to specific cell targets, which was a solution for some traditionally chemoresistant tumors. César Milstein begun a new road with the discovery of the monoclonal antibodies, opening the landscape of the immuno-oncology that lead to present check-point-inhibitors. In the last decades, mathematical oncology and the “omics” sciences, also came to help as complementary tools for the management of this extremely complex disease in the context of a personalized medicine. Indeed, the possibility of introducing information derived from these sciences into hybrid and/or multiscalar mathematical models are nowadays the approaches most interesting and promising; with good perspectives in the diagnosis, prognosis, treatment design and follow-up of different kinds of tumors. Although at present many tumor types can be completely cured, other ones are much more difficult to eradicate, and they would be better considered as chronic diseases. In this context, some new important concepts emerge in the metronomics field, as keeping a stable tumor burden, a more benign tumor grade and a good quality of life. This minireview addreses all these mentioned issues.